The mediation of HIV/AIDS knowledge in the effect of media exposure on attitude and practice on the syndrome: a cross sectional study of adolescent Islamiyya girls in North- east Nigeria - Hamid, Adamu Muhammad; Tamam, Ezhar (Universiti Putra Malaysia Press, 2018)
In the early 2000s adolescents' media exposure in sub-Saharan Africa was reported as very low, but today growth in infrastructure, media technology and program appeal make a case for a reassessment of the situation. Given that communication particularly through the media is considered a major preventive strategy to addressing the spread of the epidemic, this study investigates the media exposure, knowledge, attitude and practice (KAP) status of adolescent Islamiyya girls as potential mothers in Northeast Nigeria on HIV/AIDS as a predominantly Muslim society against the backdrop of earlier studies which showed that Muslim communities which were hitherto considered protected, were now witnessing a rapid evidence of an advancing HIV/AIDS epidemic. On the Hierarchy of Effects theory, hypotheses were posed to test relationships between HIV/AIDS media exposure and knowledge, favorable attitudes and safe practice among the girls; mediation effect of HIV/ AIDS knowledge was verified. A survey was administered on a sample of 487 Islamiyya girls in Bauchi. The study finds that while mass media exposure is not a significant predictor of HIV/AIDS safe practice and favorable attitude, it is a significant predictor of HIV/AIDS knowledge. While HIV/AIDS knowledge is a significant predictor of both HIV/AIDS favorable attitude and safe practice. There was a significant mediation effect of HIV/AIDS knowledge on the effect of HIV/AIDS media exposure on HIV/ AIDS safe practice. It was thus concluded that media exposure is a necessary but not a sufficient precursor for HIV/AIDS safe practice.